Comparative Efficacy and Safety of Prostacyclin Analogs for Pulmonary Arterial Hypertension: A Network Meta-Analysis. Issue 4 (January 2016) - Zhang, Huijun; Li, Xiaobing; Huang, Jiancheng; Li, Hongying; Su, Zhenyu; Wang, Jun
Abstract : Abstract: Prostacyclin analogs, such as epoprostenol, treprostinil, iloprost, and beraprost, have long been used for pulmonary arterial hypertension (PAH) treatment, yet their relative efficiency remains disputed. Eligible randomized controlled trials (RCTs) involving the 4 therapies mentioned above were retrieved from PubMed, Embase, and Cochrane (up to August 1, 2015). Odds ratios (ORs) were estimated for dichotomous data (mortality, functional class (FC) amelioration, and discontinuation); standardized mean differences (SMDs) with 95% confidence intervals (CIs) were estimated for continuous data (6-min walk distance [6-MWD]). Patients taking epoprostenol were anticipated to demonstrate more expedient 6-MWD than those taking placebo when network meta-analysis (NMA) was implemented (SMD = 52.19; 95% CI: 24.28–113.39), the trend of which was identical with that of pairwise meta-analysis (SMD = 69.28; 95% CI: 10.43–128.98). Nonetheless, the prominent advantages of treprostinil over placebo (SMD = 30.15; 95% CI: 19.29–40.01) in 6-MWD could not be replicated by NMA. Furthermore, direct and indirect (NMA) comparisons also differed in FC amelioration. For example, the superiority of epoprostenol over placebo as evident with the use of NMA (OR = 42.79; 95% CI: 10.63–301.98) could not be confirmed by pairwise meta-analysis. As suggested by indirect comparisons among 4 prostanoids, epoprostenol appears to result in remarkably favorable FC amelioration comparing to other regimens (all P < 0.05). Participants taking beraprost were more probable to withdraw in comparison with those administrated with iloprost (OR = 10.07; 95% CI: 1.47–160.65). Taking mortality, FC amelioration, discontinuation, and 6-MWD into account, epoprostenol could be recommended as an alternative treatment for patients with moderate/advanced PAH. Abstract : Supplemental Digital Content is available in the text